2022
DOI: 10.1093/brain/awac145
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic spectrum of ATP6V1A encephalopathy: a disorder of lysosomal homeostasis

Abstract: Vacuolar-type H+-ATPase (V-ATPase) is a multimeric complex present in a variety of cellular membranes that acts as an ATP-dependent proton pump and plays a key role in pH homeostasis and intracellular signalling pathways. In humans, 22 autosomal genes encode for a redundant set of subunits allowing the composition of diverse V-ATPase complexes with specific properties and expression. Sixteen subunits have been linked to human disease. Here we describe 26 patients harbouring 20 distinct pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Developmental and epileptic encephalopathy 93 is an autosomal dominant disorder with, among other features, delayed psychomotor and impaired intellectual developments, as well as early onset epilepsy. Additional clinical features like microcephaly and hypoplastic amelogenesis imperfecta were observed in epileptic encephalopathy ( Guerrini et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental and epileptic encephalopathy 93 is an autosomal dominant disorder with, among other features, delayed psychomotor and impaired intellectual developments, as well as early onset epilepsy. Additional clinical features like microcephaly and hypoplastic amelogenesis imperfecta were observed in epileptic encephalopathy ( Guerrini et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of the first gene underlying an amelogenesis imperfecta from mapping of AMELX in 1989 ( Lau et al, 1989 ) to its causative role in AI in 1990 ( Lagerström et al, 1990 ; 1991 ); more than 70 genes have been discovered as important for amelogenesis and its defects. The most recent ones are CLAUDIN 10 ( Sewerin et al, 2022 ) and ATP6V1A ( Guerrini et al, 2022 ) . Knowledge is evolving fast on amelogenesis ( Simmer et al, 2021 ) and enamel disturbances in rare diseases.…”
Section: Discussionmentioning
confidence: 99%
“…ATP6V1A (H + -transporting two-sector ATPase; underexpressed DEP with −2.17 FC) is part of a multimeric complex present in a variety of cellular membranes that acts as an ATP-dependent proton pump and plays a key role in pH homeostasis and intracellular signaling pathways. ATP6V1A variants, mainly clustering within the ATP synthase α/β family-nucleotide-binding domain, include early lethal encephalopathies and developmental encephalopathy in epilepsy [ 95 , 96 , 97 ]. Interestingly, several mutants of ATP6V1A , such as the p.Asp100Tyr, are characterized by reduced expression due to increased degradation; these mutations caused a defect in neurite elongation accompanied by loss of excitatory inputs, revealing that altered lysosomal homeostasis markedly affects neurite development and synaptic connectivity [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…This acidification process is crucial for lysosomal hydrolytic activity and autophagy. [ 40 , 44 , 45 ] Consistent with the downregulation of ATP6V1A, overexpression of miR‐143‐3p resulted in lysosomal de‐acidification (Figure 3I ). Moreover, this de‐acidification was accompanied by decreased enzymatic activities of CTSB and CTSD, which are two major lysosomal proteases (Figure 3J ).…”
Section: Resultsmentioning
confidence: 68%
“…Moreover, we investigated whether inhibiting the release of astrocytic EVs could suppress the increase in EVs‐miR‐143‐3p level in ICH mice. Neutral sphingomyelinase 2 (nSMase2), a product of the SMPD3 gene, is an essential enzyme for the synthesis and release of EVs [ .40 ] We specifically knockdown SMPD3 in astrocytes by stereotactically injecting AAV‐SMPD3‐shRNA that contains a GFAP‐specific promoter (Figure 2D ). Importantly, we found that after inhibiting the secretion of astrocytic EVs, the level of EVs‐miR‐143‐3p in brain pool was no longer elevated after ICH (Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%